Determinants of the microbial community structure of eutrophic, hyporheic river sediments polluted with chlorinated aliphatic hydrocarbons. Issue 3 (10th December 2013) - Hamonts, Kelly; Ryngaert, Annemie; Smidt, Hauke; Springael, Dirk; Dejonghe, Winnie
Abstract Chlorinated aliphatic hydrocarbons (CAHs) often discharge into rivers as contaminated groundwater baseflow. As biotransformation of CAHs in the impacted river sediments might be an effective remediation strategy, we investigated the determinants of the microbial community structure of eutrophic, CAH‐polluted sediments of the Zenne River. Based on PCR‐DGGE analysis, a high diversity of Bacteria, sulfate‐reducing bacteria, Geobacteraceae, methanogenic archaea, and CAH‐respiring Dehalococcoides was found. Depth in the riverbed, organic carbon content, CAH content and texture of the sediment, pore water temperature and conductivity, and concentrations of toluene and methane significantly contributed to the variance in the microbial community structure. On a meter scale, CAH concentrations alone explained only 6% of the variance in the Dehalococcoides and sulfate‐reducing communities. On a cm‐scale, however, CAHs explained 14.5–35% of the variation in DGGE profiles of Geobacteraceae, methanogens, sulfate‐reducing bacteria, and Bacteria, while organic carbon content explained 2–14%. Neither the presence of the CAH reductive dehalogenase genes tceA, bvcA, and vcrA, nor the community structure of the targeted groups significantly differed between riverbed locations showing either no attenuation or reductive dechlorination, indicating that the microbial community composition was not a limiting factor for biotransformation in the Zenne sediments.